Resurrection walk (Lincoln lawyer novel, ,, 2023)
With the help of his half-brother, retired LAPD Detective Harry Bosch, defense attorney Mickey Haller sets out to prove the innocence of a woman in prison for killing her husband, a sheriff's deputy, putting Mickey in the crosshairs of a killer who doesn't want the case reopened--or the truth coming to light.

The fifth witness: a novel (Mickey Haller novels, 4, 1, 2011)
Mickey Haller has fallen on tough times. He expands his business into foreclosure defense, only to see one of his clients accused of killing the banker she blames for trying to take away her home. Mickey puts his team into high gear to exonerate Lisa Trammel, even though the evidence and his own suspicions tell him his client is guilty. Soon after he learns that the victim had black market dealings of his own, Haller is assaulted, too, and he's certain he's on the right trail.

The law of innocence (Mickey Haller novels, 6, 1, 2020)
"Defense attorney Mickey Haller is pulled over by police, who find the body of a former client in the trunk of his Lincoln. Haller is immediately charged with murder but can't post the exorbitant $5 million bail slapped on him by a vindictive judge. Mickey elects to represent himself and is forced to mount his defense from his jail cell in the Twin Towers Correctional Center in downtown Los Angeles. All the while he needs to look over his shoulder--as an officer of the court he is an instant target, and he makes few friends when he reveals a corruption plot within the jail. But the bigger plot is the one against him. Haller knows he's been framed, whether by a new enemy or an old one. As his trusted team, including his half-brother, Harry Bosch, investigates, Haller must use all his skills in the courtroom to counter the damning evidence against him. Even if he can obtain a not-guilty verdict, Mickey understands that it won't be enough. In order to be truly exonerated, he must find out who really committed the murder and why"--

The brass verdict: a novel (Mickey Haller novels, 2, 1, 2008)
Things are finally looking up for defense attorney Mickey Haller. After two years of wrong turns, Haller is back in the courtroom. When Hollywood lawyer Jerry Vincent is murdered, Haller inherits his biggest case yet: the defense of Walter Elliott, a prominent studio executive accused of murdering his wife and her lover. But as Haller prepares for the case that could launch him into the big time, he learns that Vincent's killer may be coming for him next. Enter Harry Bosch. Determined to find Vincent's killer, he is not opposed to using Haller as bait. But as danger mounts and the stakes rise, these two loners realize their only choice is to work together.

The crossing: a novel (Harry Bosch mysteries, 18, 1, 2015)
"Detective Harry Bosch has retired from the LAPD, but his half-brother, defense attorney Mickey Haller, needs his help. The murder rap against his client seems ironclad, but Mickey is sure it's a setup. Though it goes against all his instincts, Bosch takes the case. With the secret help of his former LAPD partner Lucia Soto, he turns the investigation inside the police department. But as Bosch gets closer to discovering the truth, he makes himself a target"--